PENGARUH PELAYANAN PERPAJAKAN DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK PADA KPP PRATAMA JAKARTA SENEN TAHUN 2024 - Wardhani, Muktyara Rahma; Singgih, Rahadi Pratomo (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the effect of tax services and taxpayer compliance on tax revenue at the Jakarta Senen Pratama Tax Service Office (KPP) in 2024. Tax revenue is a major component in the State Budget (APBN), so its success is highly dependent on the effectiveness of tax services and the level of taxpayer compliance. The problems that occur at the Jakarta Senen Pratama Tax Service Office include fluctuations in tax revenue and the still low level of compliance in reporting Corporate Taxpayer SPTs, which can have implications for not achieving the revenue target. This study used a quantitative approach with a descriptive method. The sampling technique in this study was carried out using simple random sampling with a total of 100 Individual Taxpayers registered with the Jakarta Senen Pratama Tax Service Office. The data was processed using SPSS Version 27, to determine the magnitude of the influence the researcher used the F test, T test and coefficient of determination. The results of the study showed that there was a positive and significant influence of Tax Services on Tax Revenue of 62.4%. There was a positive and significant influence of Taxpayer Compliance on Tax Revenue of 53.7%. Taxation Services and Taxpayer Compliance simultaneously have a positive and significant effect on Tax Revenue at KPP Pratama Jakarta Gambir Senen by  66.7%.